2002
DOI: 10.1002/qaj.175
|View full text |Cite
|
Sign up to set email alerts
|

The long arm of the lab laws

Abstract: This paper may be viewed at the American Chemical Society's website (http://pubs.acs.org/subscribe/journals/tcaw/10/i11/html/11regs.html)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…But then, unexpectedly, the IBT laboratories were visited by inspectors from the US FDA and exposed as having systematically produced fraudulent data [21]. A few years later Craven Labs, another laboratory working for Monsanto, was exposed by a "pesticide industry task force", and the US EPA, as having committed scientific fraud [22,23]. The president of IBT was sentenced to four years in prison, but allegedly never served a day of his sentence, because "his heart was bad" [24].…”
Section: A History Of Systematic Fraudmentioning
confidence: 99%
See 1 more Smart Citation
“…But then, unexpectedly, the IBT laboratories were visited by inspectors from the US FDA and exposed as having systematically produced fraudulent data [21]. A few years later Craven Labs, another laboratory working for Monsanto, was exposed by a "pesticide industry task force", and the US EPA, as having committed scientific fraud [22,23]. The president of IBT was sentenced to four years in prison, but allegedly never served a day of his sentence, because "his heart was bad" [24].…”
Section: A History Of Systematic Fraudmentioning
confidence: 99%
“…This also led to the establishment of laboratory standards, defining first routines of Good Laboratory Practice in 1979 (following the IBT scandal). Later, a task force of inspectors was established, including a hotline for whistleblowers and new rounds of information targeted at the laboratory industry [22,23]. In a 2002 report update from the US EPA Laboratory Fraud Work Group, the EPA states; "the ramifications stemming from a laboratory's falsifications spread far beyond the specific tampered results; once the laboratory's integrity is compromised, all the data generated by that laboratory is questionable" [26].…”
Section: A History Of Systematic Fraudmentioning
confidence: 99%
“…are changed for no technically valid reason. This improper practice is usually employed to change the status of a particular task or analysis from "unacceptable" to "acceptable," eliminating the need for costly and time-consuming corrective actions that can range from resampling and reanalysis to the preparation of new calibration curves (Novak 2001). The practice can also be used to increase productivity by artificially including more analytical runs into a preset time window, thereby eliminating the labor-intensive instrument set-up and quality control analyses required for each analytical batch (Terhune n.d.).…”
Section: Time Travelmentioning
confidence: 99%
“…Unfortunately, the ethically challenged can also manually override the software for other reasons, primarily to change the status of data from "noncompliant" to "compliant" to meet with method requirements. This data falsification technique is referred to as peak juicing or shaving and involves the intentional adding or subtracting of peak areas (Novak 2001).…”
Section: Chromatographic Peak Manipulationmentioning
confidence: 99%
“…Ultimately, one defendant was sentenced to a year in prison followed by four years probation; two others were sentenced to six months in jail each and two years probation [5]. As only 214 of 1205 pesticide studies were found to be acceptable [4], the investigation forced the retesting of thousands of industrial chemicals [6]. The studies conducted on the few drugs being tested by IBT were determined to be acceptable [4].…”
Section: O Of F T Th He E G Gl Lp P R Re Eg Gu Ul La At Ti Io On Ns Smentioning
confidence: 99%